Analysis of 87 patients with Lofgren's syndrome and the pattern of seasonality of subacute sarcoidosis - Demirkok, Sevtap Sipahi; Basaranoglu, Metin; Dervis, Emine; Bal, Mert; Karayel, Tuncer (WILEY, 2006)
Background: Sarcoidosis is a multisystem disease of unknown aetiology. The seasonality of sarcoidosis in symptomatic, recently diagnosed patients with Lofgren's syndrome was evaluated to help better understand the possible causative factor(s) in the pathogenesis of sarcoidosis. Methods: Four hundred and ninety-two consecutive patients with sarcoidosis were investigated. The demographic and clinical features, course of the disease, initial diagnostic methods and both the month and age at initial diagnosis for each patient were analysed. Roger's test for cyclic variation was used to determine the significance of any seasonal variation of incidence. Results: Lofgren's syndrome was diagnosed in 87 patients (18%). The diagnosis of sarcoidosis was delayed in 45% of subjects (mean: 11.2 weeks). The distribution of cumulative monthly presentations peaked in May (spring) and was the lowest in January (winter) and November (autumn) (P < 0.001). The seasonal pattern was also influenced by age and gender (P < 0.05). At the onset, arthralgia was present in 46%, cough or dyspnoea in 37%, constitutional symptoms in 32% and skin lesions in 30% of the patients. Conclusions: In this study, there were differences in the amplitude of the seasonal variation by age and by gender. Well-designed prospective studies are required to better understand the importance of the findings we respect to the pathogenesis of the disease.
Keywords: age; gender; sarcoidosis; seasonal variation; RESPIRATORY-INFECTIONS; ASTHMA; EPIDEMIOLOGY; Respiratory System